A study among newly appointed principals in South African schools. (2019) - Botha, R.J.
The important role played by principals in ensuring effective management and strategic leadership in schools has long been the subject of intense debate. Crucial to this debate are the contextual development and support opportunities available to newly appointed principals. Although many such opportunities do exist, they are simply not sufficient to ensure sustainable school improvement. This article, based on a quantitative empirical study carried out in the Gauteng province of South Africa, aims to contribute to the discussion on the school principalship and the changes and improvements taking place at schools. The article concludes with empirical findings on the perceived developmental needs of newly appointed principals in Gauteng and goes on to suggest that this unique and specialised profession requires specific and appropriate preparation. The recommendations arising from the study concerning policy and practice emphasise the importance of appropriate and sustainable development and support initiatives for newly appointed school principals, not only in South Africa, but also world-wide.